Pentaclorofenol: toxicología y riesgos para el ambiente - Castillo Morales, Irasema; Bárcenas Pazos, Cristina (Instituto de Ecología, A.C., 2016)
Pentachlorophenol (PCP) and its salt, sodium pentachlorophenate (NaPCP) are very persistent halogenated hydrocarbons with a wide spectrum of toxicity and which are used primarily to protect timber from fungi, bacteria and insects. PCP and NaPCP are chemicals with a high acute toxicity to human beings increased substantially by impurities such as c h l o r o d i b e z o d i o x i n s a n d chlorodibenzofurans. PCP has long term adverse effects, is mutagenic, causes alterations in immunological and endocrine systems; it increases susceptibility to infections and reproductive dysfunction. There are several studies on the adverse effects of these substances on human and ecosystems health caused by its persistence, bioaccumulation potential and the toxicity of the impurities. These works are the technical basis of the severe restrictions or even total ban status of PCP and its derivatives and residues in several countries. In Mexico, PCP is authorized for forest, urban and industrial applications as a wood preserver. PCP must be purchased and used only by or with the surveillance of a certified technician. There is a significant lack of information among people about the environmental and health risks from the misuse and inadequate disposal of PCP, NaPCP and its residues. The aim of this work is to diffuse the available technical information on this subject and recommend the application of the national and international legislative regulations on PCP use.